Penyusunan Laporan Keuangan Koperasi Rimbawan Sejahtera Bersama Menggunakan Microsoft Excel Berdasarkan SAK ETAP - Novi Nurbaeti; Sudrajat; Jouzar Farouq Ishak (Jurusan Akuntansi Politeknik Negeri Bandung, 2023)
This research was conducted on the Cooperative Rimbawan Sejahtera Bersama, which has not yet prepared financial statements. This study aims to determine the preparation of the financial statements of the Cooperative Rimbawan Sejahtera Bersama using Microsoft Excel based on SAK ETAP. This study used descriptive qualitative method. The method of collecting data in this study is through interviews, documentation and observation. Results of this study is the design of simple financial reporting applications using Microsoft Excel 2016 to assist in the preparation of financial statements in accordance with the SAK ETAP month of February 2021.